2020
DOI: 10.1182/blood-2020-136292
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ixazomib Induction and Maintenance in Newly Diagnosed Multiple Myeloma Patients According to the IMWG Frailty Score: A Post-Hoc Analysis of the EMN10-Unito Trial

Abstract: INTRODUCTION. Elderly patients (pts) with newly diagnosed multiple myeloma (NDMM) are a heterogeneous population. The IMWG frailty score stratifies pts ≥65 years into 3 categories (fit, intermediate-fit and frail), according to chronological age, comorbidities and functional abilities, with different prognosis. We previously reported results from the phase II EMN10-Unito study investigating 4 Ixazomib-based induction regimens followed by Ixazomib maintenance in elderly NDMM pts. Here we present a post-hoc anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The proportion of patients with Grade 3 or 4 AEs (19%) and non-hematological AEs (29%) observed in this study was comparable to that of EMN10 (47% and 37%, respectively), but was lower than that of the HOVON-143 trial (74% and 73%, respectively) and MAIA trial (DRd: 94.6% and 83.9%; Rd: 89.2% and 81.9%, respectively) analyzed in frail NDMM patients. 7 , 10 , 31 The younger age of the patients in this study could partly explain the difference observed with the latter two trials (71 vs. 81 vs. 77 years in this study, HOVON-143 study, and MAIA study, respectively), which led to less comorbidity. The regimen without daratumumab could also partly explain this difference.…”
Section: Discussionmentioning
confidence: 61%
“…The proportion of patients with Grade 3 or 4 AEs (19%) and non-hematological AEs (29%) observed in this study was comparable to that of EMN10 (47% and 37%, respectively), but was lower than that of the HOVON-143 trial (74% and 73%, respectively) and MAIA trial (DRd: 94.6% and 83.9%; Rd: 89.2% and 81.9%, respectively) analyzed in frail NDMM patients. 7 , 10 , 31 The younger age of the patients in this study could partly explain the difference observed with the latter two trials (71 vs. 81 vs. 77 years in this study, HOVON-143 study, and MAIA study, respectively), which led to less comorbidity. The regimen without daratumumab could also partly explain this difference.…”
Section: Discussionmentioning
confidence: 61%
“…The most commonly used tool for frailty assessment was the IMWG frailty score (18/43, 41.8%). Among the RCTs, IMWG frailty score was used or is currently being used in a total of 6 NDMM studies (Larocca et al [ 25 ], EMN10 [ 26 ], UK FiTNEss [ 27 ], MM4 [ 28 ], EMN01 [ 29 ], IFM 2017_03 [ 30 ]). Among the non-RCTs, the IMWG frailty score was utilized in 12 studies (8 NDMM and 4 R/R).…”
Section: Resultsmentioning
confidence: 99%
“…Mina et al demonstrated, with data from the EMN10-Unito study, that 25.1% of patients had frailty and reduced OS. Moreover, adverse events, dose modifications, and therapy discontinuation were more frequent in frail patients [ 19 ]. However, they showed similar overall response rates and very good partial response and progression-free survival, irrespective of frailty status [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adverse events, dose modifications, and therapy discontinuation were more frequent in frail patients [ 19 ]. However, they showed similar overall response rates and very good partial response and progression-free survival, irrespective of frailty status [ 19 ]. Stege et al reported in a study of 65 frail patients with newly diagnosed MM that the 12-month OS in the study population was 78% and median progression-free survival was 13.8 months [ 20 ].…”
Section: Discussionmentioning
confidence: 99%